From Bar to Sportainment: The Role of Strategic Communication in Holywings' Brand Transformation - Dewantari, Nurul Shanty (Enigma in Economics, 2024)
The strategic transformation of brands in the digital age necessitates a dynamic and multifaceted approach to communication. The case of Holywings, an Indonesian establishment that successfully transitioned its brand identity from a conventional bar to a prominent player in the sportainment industry, exemplifies this phenomenon. The research employed a qualitative methodology, incorporating in-depth interviews with key stakeholders and a comprehensive content analysis of Holywings' social media presence. The interviews provided insights into the strategic rationale and communication tactics employed, while the content analysis examined the types of content shared, engagement metrics, and overall communication style. The findings revealed a multifaceted strategic communication approach, leveraging both digital and traditional marketing channels. Social media platforms, particularly Instagram and TikTok, played a pivotal role in showcasing Holywings' sportainment offerings and fostering audience engagement. The content strategy focused on sports-centric events, behind-the-scenes glimpses, and interactive elements, amplified by the use of gimmicks, drama, and storytelling. The integration of offline activations further enhanced the brand experience, fostering a sense of community and loyalty. The strategic communication efforts yielded a significant shift in brand perception, successfully repositioning Holywings as a leader in the sportainment industry. The omnichannel engagement model facilitated a seamless and personalized customer experience, driving brand advocacy and repeat business. In conclusion, the study underscores the pivotal role of strategic communication in shaping brand perception, navigating the complexities of brand transformation, and achieving sustainable growth in the digital age. The findings highlight the importance of adaptability, innovation, and a customer-centric approach in crafting a compelling brand narrative and fostering meaningful connections with the target audience.